Analisis Karakteristik Permukiman Desa-Desa Pesisir di Kabupaten Kulonprogo - Marwasta, Djaka; Priyono, Kuswaji Dwi (Universitas Muhammadiyah Surakarta, 2007)
Settlement is the most important area in the activity of disaster mitigation. The Biggest detriment caused by disaster is generally placed at the settlement or residential area. Thereby, the identification of the settlement characteristics is required to be able to recognize the disaster risk. This research aim to identify the characteristics of the rural settlement on the coastal area in the District of Kulonprogo. This area is chosen based on the consideration of coastal morphological characters. This area have slopeslightly coastal zone which face to Indonesian Ocean. In this situation, hence in the event of tidal wave, there will be wide spread overflowing run up water. Two approaches is used in this research, they are; (1) Morphological Approach, and (2) Behaviour Approach. Both of the approaches is conducted with comparative perspective. The existance of the settlement which have been filtered through settlement and coastal tipology are compared. The data are collected and analyzed through: (1) Mapping and GIS tools; (2) survey method; (3) Indepth interview; and (4) statistical analysis. Thirty household are selected proportionally to setlement unit as a respondent in indepth interview. In order to analyze the data, descriptive analysis (frequency tables) and crossed tables are used. This research indicate that rural settlements on the coastal area in the District of Kulonprogo are spatialy distributed as a ribbon pattern. This pattern are coincident with the shape of the coast and the linearity of the road as well. Most of the buildings are in good condition, and they characterized by moderate housing density. In the term of coastal morphology, the research area is dominated by sandy coast with slopeslightly relief. Generally, the socio economic condition of the peoples living there are low to medium economic level, low education, and rarely medium income. Related to tidal flood vulnerability, this research area is the second level (moderate) hazardeous zone.